METHODOLOGY FOR DEVELOPING STUDENT DISCOURSE THROUGH PARALLEL CORPORA - Karimova Fotima Kamoliddin qizi (Bright Mind Publishing, 2025)
This article analyzes the methodology of using parallel corpora in developing student discourse. The use of parallel corpora is considered an effective tool for optimizing the language learning process, analyzing lexical and grammatical units in context, and forming students' communicative competence. The article discusses in detail the stages of working with parallel corpora, types of exercises, and methods for assessing results.
Keywords: Parallel corpus, discourse, linguistic analysis, translation skills, communicative competence.